EDUKASI LITERASI MEDIA SOSIAL SEBAGAI UPAYA PENCEGAHAN HOAKS DI KALANGAN MAHASISWA UNIVERSITAS DHARMWANGSA - Zulkifli Zulkifli; Haslinda Haslinda; Zacky Daffa Athala (MAJU : Indonesian Journal of Community Empowerment, 2026)
The growth of social media platforms has facilitated the access and dissemination of information. However, the increasing use of social media has also heightened the risk of hoaxes—false information that can influence people's thinking, attitudes, and actions—particularly among university students, who are active users of digital technology. A lack of skills in evaluating and verifying information makes students susceptible to exposure to hoaxes and contributes to their further dissemination. This activity aims to enhance the understanding and skills of Dharmawangsa University students regarding the identification of hoax characteristics, the verification of information, and the application of ethical standards in social media usage. The approach employed includes information sessions, interactive lectures, group discussions, case study analyses, fact-checking simulations, and assessments via pre- and post-tests. The material covers digital media literacy, the characteristics of hoaxes, information verification methods using credible sources, and the importance of ethics in digital communication. The results indicate an improvement in students' understanding and awareness regarding the risks associated with hoaxes and the importance of verifying information before sharing it with others. Students also demonstrated improved skills in identifying credible information and exhibited greater responsibility in their social media usage. This social media literacy program has proven effective in fostering a critical, intelligent, and ethical digital culture within the higher education environment. The activity is expected to serve as a model for ongoing education to support the creation of a healthy information ecosystem among students.